2006
DOI: 10.1089/scd.2006.15.141
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Express Neural Genes, Suggesting a Neural Predisposition

Abstract: Because of their unique attributes of plasticity and accessibility, bone marrow-derived mesenchymal stem cells (MSCs) may find use for therapy of neurodegenerative disorders. Our previous studies of adult human MSCs demonstrated that these cells express an extensive assortment of neural genes at a low but clearly detectable level. Here, we report expression of 12 neural genes, 8 genes related to the neuro-dopaminergic system, and 11 transcription factors with neural significance by human MSCs. Our results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 132 publications
7
103
0
Order By: Relevance
“…However, several recent reports have shown the differentiation capabilities of MSCs toward the neural lineages under specific medium conditions [31][32][33][34][35][36][37]. Our group has previously shown [6], as have others [38,39], that MSCs basally express several neural markers and NTFs. We have also shown that under specific conditions, MSCs can differentiate into dopamine-producing cells that express neuronal markers [40 -42].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, several recent reports have shown the differentiation capabilities of MSCs toward the neural lineages under specific medium conditions [31][32][33][34][35][36][37]. Our group has previously shown [6], as have others [38,39], that MSCs basally express several neural markers and NTFs. We have also shown that under specific conditions, MSCs can differentiate into dopamine-producing cells that express neuronal markers [40 -42].…”
Section: Discussionmentioning
confidence: 67%
“…These cells are considered as candidates for neurodegeneration therapeutics since they express neural markers at their basal level, a fact that probably contributes to their neural-like differentiation capabilities [6]. Two advantages of MSCs are that they can be easily obtained and autotransplanted.…”
Section: Introductionmentioning
confidence: 99%
“…As alluded to earlier, cells within MSC cultures have been observed to express genes and proteins associated with key neural behaviors, including neural development, differentiation, neurotrophic factor secretion and sensing, axon guidance, and synapse formation [46][47][48][49][50]. Whereas the expression of neural markers by MSCs could be interpreted as solely a reflection of a predisposition toward the neuroectodermal lineage, it is also possible that some of these genes and proteins play roles in MSC function in the bone marrow, perhaps as regulators of hematopoiesis.…”
Section: The Controversy Of Msc Transdifferentiationmentioning
confidence: 89%
“…It was discovered that MSCs express a considerable repertoire of neural genes, which likely contributes to the contested neurogenic predisposition of these cells [46][47][48][49][50]. Indeed, recent publications show that marrow-derived neuronal-like cells exhibit some typical neuronal electrophysiological traits [51][52][53][54][55][56].…”
Section: The Controversy Of Msc Transdifferentiationmentioning
confidence: 99%
“…hMSCs express several surface epitopes with the majority of the cells being in the G 0 /G 1 phase (Yamaguchi et al, 2001) . They are notable for their ability to self-proliferate and differentiate along multiple lineages including bone, cartilage, adipose and muscle cells (Pittenger et al, 1999;Jiang et al, 2002;Shi et al, 2002;Simonsen et al, 2002), with other researches showing that the cultured hMSCs also have the potential to differentiate into neural cells (Sanchez-Ramos et al, 2000;Woodbury et al, 2000;Xiang et al, 2001a;Blondheim et al, 2006). hMSCs can be easily isolated, cultured and expanded in vitro due to their adherent characteristics.…”
Section: Introductionmentioning
confidence: 99%